Upgrading pine sawdust pyrolysis oil to green biofuels by HDO over zinc-assisted Pd/C catalyst. (1st May 2016) - Huang, Yinbin; Wei, Lin; Zhao, Xianhui; Cheng, Shouyun; Julson, James; Cao, Yuhe; Gu, Zhengrong
Highlights: The Pd/Zn synergistic catalysis was employed. The true pyrolysis oil as substrate was used in HDO. The products (gas and liquid) were analyzed. The optimal reaction conditions were obtained. Abstract: Upgrading pyrolysis oil by hydrodeoxygenation (HDO) is a promising route for the production of advanced biofuels. The proper reaction conditions and catalysts are important for the success of this process. Previously our research group investigated the ratio of Zn and Pd on the synergistic effect for HDO bio-oil upgrading. This present research focuses on determining the optimal reaction conditions for HDO conversion of pyrolysis oil produced from pine sawdust. Temperatures of 150, 200 and 250 °C and hydrogen pressures of 1.38, 2.76 and 4.14 MPa were evaluated. Syngas, liquids and coke were the primary products evaluated. Syngas was characterized using a Gas chromatography (GC). The liquids were characterized using a Gas chromatography–mass spectrometry (GC–MS). Increasing reaction temperature resulted in increased coke yields. Treatment at 250 °C and 1.38 MPa resulted in the highest hydrocarbon content (6.06%). The treatment at 200 °C and 1.38 MPa produced the largest amounts of hydrocarbons in C6 –C12 range (5.07%). The physicochemical characterizations further support the GCMS results. Syngas analysis revealed that higher hydrogen pressure leads to increased hydrogen consumption and results in more oxy-compounds conversion to hydrocarbons. The syngas analysis also supports the liquid analysis result.